A novel acidic polysaccharide from blackened jujube: Structural features and antitumor activity in vitro - Zhang, Guifeng; Liu, Chuang; Zhang, Rentang (Frontiers in Nutrition, 2022)
Liver cancer is one of the most common cancers, with increasing trends in incidence and mortality. A novel acidic polysaccharide (BJP-2) obtained from blackened jujube was extracted by hot water followed by chromatographic purification employing DEAE-cellulose 52 and Sephadex G-100 column. And then BJP-2 was identified by SEC-MALLS-RI, GC-MS, methylation and NMR for the following characteristics: molecular weight of 6.42 × 104 Da, monosaccharide composition of glucuronic acid (GalA), arabinose (Ara), galactose (Gal), rhamnose (Rha), xylose (Xyl), glucuronic acid (GlcA), glucose (Glc), fucose (Fuc) and mannose (Man) with the percentage of 39.78, 31.93, 16.86, 6.43, 1.86, 1.28, 1.02, 0.61, and 0.23%, as well as the main chain of → 5)-α-L-Araf (1 → 4)-β-D-Gal(1 → , T-α-L-Araf (1 → 4)-β-D-Gal(1 → , and → 4)-α-L-6MeGalAp(1 → . The effect of BJP-2 on the apoptosis of HepG2 cells and its anti-tumor mechanism were further explored. The analysis by MTT and flow cytometry showed that BJP-2 suppressed cell proliferation by inducing apoptosis in a concentration-dependent manner. Cell scratching and Transwell revealed that BJP-2 was able to block the invasion and metastasis of tumor cells. Western blot results demonstrated that BJP-2 exhibited antitumor activity through a mitochondria-dependent pathway, as evidenced by overexpression of Bax, Cleaved Caspase-3/Caspase-3 and Cleaved Caspase-9/Caspase-9 and downregulation of Bcl-2. Therefore, BJP-2 has broad research prospects as a tumor preventive or therapeutic agent.